Rendimento e qualidade física e fisiológica de sementes de azevém submetido à dessecação em pré-colheita e manejos de adubação nitrogenada - Müller, Caren Alessandra (2023)
Ryegrass (Lolium multiflorum Lam.) is an annual grass that can be used in succession with summer crops such as soybeans and corn, intended as soil cover in the no-tillage system or to fill the forage gap in the autumn and winter months in the south of Brazil in the crop-livestock integration system. The objective of this work was to verify the effect of pre-harvest desiccation on ryegrass, using herbicides with different mechanisms of action and to study the effect of nitrogen fertilization management on the yield components and physical and physiological quality of ryegrass seeds. In the first field experiment, with the cultivar BRS Ponteio, the herbicides glufosinate, glyphosate, dicamba + glyphosate, 2,4-D + glyphosate, carfentrazone and clethodim were used, which were applied on 21, 26 and 31 days after flowering ( DAF) of ryegrass and a control treatment without herbicide application. The second experiment was conducted over two years and subjected to nitrogen (N) fertilizer management at a dose of 100 kg N ha-1 : [1] no application; [2] 100% at the beginning of tillering; [3] 50% at the beginning of tillering and 50% at full tillering; [4] 50% at the beginning of tillering and 50% at elongation; [5] fractionation in three applications of 33.33% at the beginning of tillering, full tillering and elongation. The results indicate that desiccation provided earlier harvest and, among the herbicides, glufosinate provided rapid plant senescence and low natural threshing, compared to the control without application. Desiccation with glufosinate also provided greater seed germination (92%) when applied at 26 DAF, no different from the association of dicamba and 2,4-D with glyphosate. This same herbicide association showed germination between 84 and 90%, regardless of the time of application, with no significance for germination and natural threshing. On the other hand, the herbicide clethodim negatively affected the physiological quality of seeds, regardless of the time of application, reducing germination by up to 75%. In the second experiment, there was an increase in seed productivity with nitrogen management in relation to the control, with an estimate of 1836 and 2306 kg ha-1 , for the first and second year, respectively, however, between the application management there was no significant effect. The application of nitrogen provided an increase in the physiological quality of seeds, about the control, with an estimated increase of 30 and 41% in germination in the first and second year, respectively, in addition to having a greater effect on the mass of a thousand seeds, especially when is applied close to elongation. Therefore, pre-harvest desiccation with glufosinate provides early harvest and maximum physiological quality of seeds, when applied at 26 DAF, and can be used in the production of ryegrass seeds. The application of nitrogen, regardless of application management, can provide an increase in productivity and a positive effect on the physical and physiological quality of seeds.